2021
DOI: 10.1002/mc.23357
|View full text |Cite
|
Sign up to set email alerts
|

Rapalogs induce non‐apoptotic, autophagy‐dependent cell death in HPV‐negative TP53 mutant head and neck squamous cell carcinoma

Abstract: TP53 is the most frequently mutated gene in head and neck squamous cell carcinoma (HNSCC). Patients with HPV-negative TP53 mutant HNSCC have the worst prognosis, necessitating additional agents for treatment. Since mutant p53 causes sustained activation of the PI3K/AKT/mTOR signaling pathway, we investigated the effect of rapalogs RAD001 and CCI-779 on HPV-negative mutTP53 HNSCC cell lines and xenografts. Rapalogs significantly reduced cell viability and colony formation. Interestingly, rapalogs-induced autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Treatment with everolimus significantly inhibited the growth of TP53 mutant cell lines and attenuated the growth kinetics of tumor-cell xenografts. In accordance with our previous studies [35], everolimus inhibited mTORC1 activity by downregulating P-mTOR S2448, P-S6 S235/236, and 4EBP1 T70. Moreover, both in cell lines and xenografts, P-STAT3, HIF-1α, VEGF-A and VEGF-C were downregulated with everolimus treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Treatment with everolimus significantly inhibited the growth of TP53 mutant cell lines and attenuated the growth kinetics of tumor-cell xenografts. In accordance with our previous studies [35], everolimus inhibited mTORC1 activity by downregulating P-mTOR S2448, P-S6 S235/236, and 4EBP1 T70. Moreover, both in cell lines and xenografts, P-STAT3, HIF-1α, VEGF-A and VEGF-C were downregulated with everolimus treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The intervention of these oncological processes might also halt the progression of TP53 mutant HNSCC, which has not been explored in this current study. Previous work from our lab has shown that everolimus induces autophagy-dependent cell death (ADCD) in TP53 mutant HNSCC through tumor cell-intrinsic mechanisms [ 35 ]. This study demonstrated that everolimus inhibits tumor angiogenesis and lymphangiogenesis through the downregulation of HIF-1α within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin (20 mg/kg body weight) or POH (50 mg/kg body weight) diluted in olive oil was injected intraperitoneally daily on day 8 for a total of 12 days, and rituximab (4 mg/kg body weight) was injected intraperitoneally on day 9 on 3 occasions 4 days apart (Q4D). Tumor size was measured with calipers, and tumor volume was calculated by the following formula: (width) 2 × length/2 ( 13 , 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…37 RAD001 also prevented tumor growth of cells with HPV-negative TP53 mutation in vivo through autophagy activity. 317 The novel mTOR inhibitors CZ415, AZD8055, OSI-027 (ASP4876), and CC-223 monotherapy inhibited HNSCC cell growth in vivo. [318][319][320] mTOR monotherapy and combination with other treatment regimens all demonstrated promising effects on the HNSCC xenograft model.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%